2019
DOI: 10.1371/journal.pone.0223236
|View full text |Cite
|
Sign up to set email alerts
|

Factors restraining the population growth of Varroa destructor in Ethiopian honey bees (Apis mellifera simensis)

Abstract: Worldwide, the ecto-parasitic mite Varroa destructor has been assigned as an important driver of honey bee (Apis mellifera) colony losses. Unlike the subspecies of European origin, the honey bees in some African countries such as Uganda and Ethiopia may not be as threatened or suffer less from mite-infestations. However, only little is known about the factors or traits that enable them to co-exist with the mite without beekeepers’ intervention. Hence, this study was designed to investigate these factors or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 65 publications
3
29
1
Order By: Relevance
“…Beekeeping is unique in Africa since it is the only global region that has large, genetically diverse populations of native honey bees (Apis mellifera) still thriving in the wild 45 . In fact, numbers of managed hives are increasing in many African countries due to limited colony losses and managed honey bee populations relatively resilient to Varroa mite 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Beekeeping is unique in Africa since it is the only global region that has large, genetically diverse populations of native honey bees (Apis mellifera) still thriving in the wild 45 . In fact, numbers of managed hives are increasing in many African countries due to limited colony losses and managed honey bee populations relatively resilient to Varroa mite 46 .…”
Section: Resultsmentioning
confidence: 99%
“…V. destructor and the tracheal mite Acarapis woodi are present in Ethiopia (Pirk et al 2015), but no studies on colony losses linked to them are available. In fact, a study by Gebremedhn et al (2019) indicated that observed Ethiopian (Tigray region) bee colonies had very low brood infestation levels. From 6727 analysed brood cells, only 133 mites were found and from those, only 18.8% were capable of reproducing, supporting our knowledge that African honey bees successfully cope with the varroa mite.…”
Section: Honey Bee Management and Bee Healthmentioning
confidence: 99%
“…Table S5. Link between 'hygienic behaviour towards dead brood' and colony survival or infestation level reported in literature [42,97,172,183,185,215,231,270,312,315,319,320,324,325,327,328,340,[349][350][351][352][353][354][355][356][357][358][359][360][361][362][363][364][365][366]. Table S6.…”
Section: Supplementary Informationmentioning
confidence: 99%